Audit atas Biaya Perkara dalam Laporan Keuangan Mahkamah Agung dan Badan Peradilan yang Berada di Bawahnya - Sipayung, Baren; Prasetyo, Agus (CV. Kalimasada Group, 2023)
Law enforcement and justice are very important parts of a society. Law enforcement and justice are represented by the state through the authority of an official institution called the judiciary. Judiciary is the process of handling = cases and the absolute authority of the court is to examine, decide and resolve cases submitted to it. Proceedings in court, especially in civil cases, are subject to fees. The basis for imposing court fees is the provisions of Article 121 paragraph (4) HIR and Article 145 paragraph (4) RBg. Therefore, the principle that is adhered to is that there is no fee, no case, except in a situation where one is unable to pay the court fee so that a case can be brought for free or prodeo as stipulated in article 237 HIR and article 237 RBg. Indications of corruption in the management of case fees began to emerge in line with BPK's findings in the 2004-2006 Central Government Financial Report (LKPP). The results of the audit showed that there were a number of illegal accounts at the Supreme Court. Nine accounts from LKPP 2005, recorded in the name of the Chief Justice of Rp 7.45 billion. In its analysis, the BPK suspects that these illegal accounts came from court fees. This is what made the BPK want to audit the case fees at the Supreme Court. This study aims to determine the audit of court costs in the financial statements of the Supreme Court and the judiciary under it. The type of research used is normative (doctrinal) legal research. Data collection techniques through library research (library research). Literature research was conducted by collecting primary data and secondary data. The data analysis used is qualitative analysis. The results of the research include (a) Management of Case Settlement Process Costs at the Court of Appeal and Unorderly Registrar's Office, (b) There are records/bookkeeping of down payment management of case fees that are not fully adequate. (c) Interest on a savings account for case processing fees that have not been deposited into the state treasury. The Process Cost Treasurer has not kept complete bookkeeping.